American Politics and Government A Bibliography of Selected Reference Materials - McAndrew, Janet M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
This annotated bibliography represents selected references in political science with an emphasis on the U.S. political system, elections, the Presidency, and Congress. This is designed for use by undergraduate students to aid them in beginning research on various political science topics dealing with American politics and government. The majority of sources are post-1990, but exceptions were made for material deemed useful for retrospective research. Topics include: (1) "Research Aids" (2 items); (2) "Bibliographies" (5 items); (3) "Dictionaries" (6 items); (4) "General Government Information" (4 items); (5) "Retrospective" (2 items); (6) "Elections" (5 items); (7) "Statistics" (3 items); (8) "The Presidency" (6 items); (9) "Congress" (10 items); and (10) "Biography" (8 items). (Author/EH)
Students.
Microfiche.
Keywords: Annotated Bibliographies; Constitutional History; Constitutional Law; Government (Administrative Body); Higher Education; Libraries; Library Collections; Politics; Presidential Campaigns (United States); Presidents of the United States; United States History; Reference Materials, Bibliographies